THE MODEL OF THE UNITARY STATE OF THE REPUBLIC OF INDONESIA IN THE REFORMATION ERA - Arif Ramadhan, Farhan (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
According to Article 1 Paragraph (1) of the 1945 Constitution, Indonesia is a unitary state and a Republic. Article 37 Paragraph (5) confirms that the form of Indonesia as a unitary state cannot be changed. There are two types of unitary states: those with a centralized system and those with a decentralized system. The unitary state with a decentralized system has five variations: (1) a unitary state with a centralized decentralized system; (2) a unitary state with a decentralized system that further decentralizes; (3) a unitary state with a proportional decentralized system; (4) a unitary state with a federalistic decentralized system; and (5) a unitary state with a confederate decentralized system. The Republic of Indonesia currently operates under a unitary state model with a decentralized system. This system was established through the enactment of Law No. 22 of 1999 and Law No. 32 of 2004, which introduced a federalistic decentralized system. However, with the implementation of Law No. 23 of 2014 concerning Local Government, the country shifted to a unitary state model with a centralized decentralization system. Keywords: Indonesia, Unitary Republic, Decentralized System